The Impact of M&A on Acquiring Firm Performance and Shareholder Value: Evidence from Thailand Market - Lertrungsi, Chawakorn (2015)
This study examines the impacts of merger and acquisition (M&A) announcements on the acquiring firms listed on the Stock Exchange of Thailand (SET). According to prior studies, the evidence for the effect of M&A on the return of acquirers is still mixed. Therefore, this research has been carried out to explore this issue in a Thai context; whether or not M&As lead to positive or negative returns on the acquiring firms’ shareholders.